Phase II study of the American Brachytherapy Society guidelines for the use of high–dose rate brachytherapy in the treatment of cervical carcinoma: is 45–50.4 Gy radiochemotherapy plus 31.8 Gy in six fractions high–dose rate brachytherapy tolerable?. Issue 1 (1st January 2006) - Shakespeare, T. P.; Lim, K. H.C.; Lee, K. M.; Back, M. F.; Mukherjee, R.; Lu, J. D.
Abstract : In 2000, the American Brachytherapy Society (ABS) published incompletely evaluated guidelines for curative chemoradiation and high–dose rate (HDR) brachytherapy for cervical cancer: our aim was to assess guideline tolerability in an Asian population. From 2000, all stage I–IVA cervical carcinoma patients were treated following ABS guidelines. Early disease (FIGO stage I/II <4 cm) received 45 Gy whole-pelvis external-beam radiation (EBRT) at 1.8 Gy/fraction, while advanced-stage disease received 50.4 Gy: no central shielding was used. All patients were planned to receive chemotherapy during EBRT, cisplatin 40 mg/m 2 weekly. All patients received 31.8-Gy HDR brachytherapy (six fractions of 5.3 Gy/fraction) to point A via three-channel applicators. Radiotherapy was completed within 8 weeks. Toxicity scoring used Common Toxicity Criteria. Nineteen of 21 (90.4%) patients (8 early, 13 advanced stage) received planned radiation, and 85.7% received planned chemotherapy. Median follow-up was 24 months (range 9–50 months). Three-year overall survival (S) was 79.1% and disease-free survival (DFS) was 64.8%. S/DFS for early and advanced stage was 85.7%/85.7% and 73.3%/47.1%, respectively. Complete response (CR) was achieved by 85.7% of patients, partial response 14.3%. For those in CR, there were no local failures. Acute cystitis occurred in 23.8%, proctitis 4.8%, and gastroenteritis 47.6%. Late cystitis occurred in 9.5%, gastroenteritis 4.8%, and genitourinary fistula (in the presence of progressive disease) 4.8%. No grade 3/4 treatment-related toxicity occurred. The ABS guidelines were well tolerated and efficacious in our study, although longer follow-up is required. Further studies are warranted to validate safety and efficacy of the recommendations.